Mediastinal Hibernoma: A Rare Case with Radiologic-Pathologic Correlation. (29th August 2016) - Darke, Maxine; Dasyam, Anil; Then, Matthew; Varma, Kavita; Borhani, Amir A.; Varma, Rakesh
Abstract : Hibernomas, especially located in the mediastinum, are extremely rare benign tumors, which are important to consider in the differential diagnosis of a heterogeneously enhancing mass with areas of fat attenuation on imaging of an often incidentally discovered mass. Other common possibilities in the differential include malignant tumors, such as liposarcoma, hence histopathology is usually required to confirm the diagnosis. Hibernomas often follow the distribution of sites of persistence of brown fat in adults, and intrathoracic locations are unusual. We present a very rare case of a mediastinal hibernoma in a 53-year-old woman. She presented to the emergency department with severe, progressive right neck and shoulder pain with radiation down her arm and was found to have a right apical posterior mediastinal mass on imaging. Initial radiographs of the shoulder showed a soft tissue mass within the apical right hemithorax. Further imaging with CT revealed a well circumscribed, heterogeneously enhancing mass with areas of fat attenuation. Pathology confirmed the diagnosis of mediastinal hibernoma, and the mass was completely excised. Fourteen months after surgery, the patient had a normal chest radiograph, and thirty-two months after surgery, she remains asymptomatic.